2011
DOI: 10.1103/physrevlett.106.033401
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Transfer-Mediated Decay and Interatomic Coulombic Decay from the Triply Ionized States in Argon Dimers

Abstract: We report the first observation of electron-transfer-mediated decay (ETMD) and interatomic Coulombic decay (ICD) from the triply charged states with an inner-valence vacancy, using the Ar dimer as an example. These ETMD and ICD processes, which lead to fragmentation of Ar(3+)-Ar into Ar(2+)-Ar(2+) and Ar(3+)-Ar+, respectively, are unambiguously identified by electron-ion-ion coincidence spectroscopy in which the kinetic energy of the ETMD or ICD electron and the kinetic energy release between the two fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…Also, it is known that there are many variants of ICD, such as ICD from satellite states [4][5][6][7], ICD after Auger decay [8][9][10][11][12][13][14], resonant ICD [15][16][17] where inner-valence excited states decay via ICD-like spectator decay, and three-electron ICD [18,19] where two inner-valence holes in a species are filled by ICD in which three electrons are involved. Another exotic variant, called electron-transfer-mediated decay (ETMD), was also predicted [20] and observed [21,22].…”
Section: Introductionmentioning
confidence: 98%
“…Also, it is known that there are many variants of ICD, such as ICD from satellite states [4][5][6][7], ICD after Auger decay [8][9][10][11][12][13][14], resonant ICD [15][16][17] where inner-valence excited states decay via ICD-like spectator decay, and three-electron ICD [18,19] where two inner-valence holes in a species are filled by ICD in which three electrons are involved. Another exotic variant, called electron-transfer-mediated decay (ETMD), was also predicted [20] and observed [21,22].…”
Section: Introductionmentioning
confidence: 98%
“…In ETMD (see Fig. 1) a neighbor donates an electron to the ion, while the released energy is simultaneously transferred either to the donor or to another neighboring species ionizing an additional electron [18][19][20]. Therefore, the neutralization of ions via ETMD is accompanied by an increase in the charge state of the complete system.…”
mentioning
confidence: 96%
“…Such ions may be obtained, for example, in the electron shakeoff process or if more than one electron is emitted in the Auger decay (double Auger process) [38]. Indeed, the ETMD(2) process of triply ionized Ar has been recently observed following Auger decay in Ar dimers [20]. Alternatively, multiply charged ions may be produced after Auger decay of cationic species.…”
mentioning
confidence: 97%
“…Therefore, previous work on the interatomic decay in rare-gas clusters showed that ICD proceeds on a timescale of tens of femtoseconds compared to the picosecond timescale of ETMD [16]. As a result, ETMD is usually observed if the decaying state does not have enough excess energy to decay by ICD [17,18]. This was specifically demonstrated to be the case for multiply charged ions produced in clusters by the Auger decay process [19].…”
mentioning
confidence: 99%